2001
DOI: 10.1007/s002590100554
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of head and neck cancer with 18F-FDG PET: a comparison with conventional methods

Abstract: The aim of this study was to evaluate the usefulness of 18F-FDG PET in the diagnosis and staging of primary and recurrent malignant head and neck tumours in comparison with conventional imaging methods [including ultrasonography, radiography, computed tomography (CT) and magnetic resonance imaging (MRI)], physical examination, panendoscopy and biopsies in clinical routine. A total of 54 patients (13 female, 41 male, age 61.3+/-12 years) were investigated retrospectively. Three groups were formed. In group I, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 11 publications
1
77
0
3
Order By: Relevance
“…11,12 In the last few years, the superior sensitivity and specificity of [ 18 F]FDG-PET compared with other imaging modalities such as computed tomography (CT) or magnetic resonance imaging scans (MRI) have been reported. [13][14][15][16] Recently, Wong et al 17 confirmed the successful diagnostic performance of [ 18 F]FDG-PET in a large series of patients with various malignancies of the head and neck. They demonstrated the principal prognostic value of overall PET interpretation and glucose uptake measured via the standardized uptake value (SUV).…”
mentioning
confidence: 68%
“…11,12 In the last few years, the superior sensitivity and specificity of [ 18 F]FDG-PET compared with other imaging modalities such as computed tomography (CT) or magnetic resonance imaging scans (MRI) have been reported. [13][14][15][16] Recently, Wong et al 17 confirmed the successful diagnostic performance of [ 18 F]FDG-PET in a large series of patients with various malignancies of the head and neck. They demonstrated the principal prognostic value of overall PET interpretation and glucose uptake measured via the standardized uptake value (SUV).…”
mentioning
confidence: 68%
“…Both were devoid of metastases on pathological examination and corresponded to inflammatory LN containing scarce focal iron deposits. changes also demonstrate an increased glucose metabolism, leading to false positive results (31). Other causes of false-positive nodes are possible and have been previously described, such as those related to the administration of lower doses of USPIO agents (17), the presence of necrosis or fatty metaplasia, a feature that can be found in about 5% of nodes (28,32).…”
Section: Discussionmentioning
confidence: 96%
“…(191). PET is a functional imaging modality assessing the metabolic status of tumors and has proved superior to CT and MRI in differentiating recurrence from post-radiation effects or scar in patients with carcinoma of the larynx (191,192). A negative PET scan excludes recurrence with a high certainty.…”
Section: ! -Mrimentioning
confidence: 99%